HEALTH-SEEKING BEHAVIOR FOR MENTAL DISORDER PATIENTS - Muryani, Ni Made Sri; Daryaswanti, Putu Intan; Putra, I Gede Yudiana (International Journal of Psychosocial Rehabilitation, 2020)
The belief of the Balinese people towards the causes of mental disorders and the quality of medical health services for mental disorder patients affects the community in seeking health for them. The purpose of this study is to explore in-depth the meaning of health-seeking behavior for mental disorder patients. This study used a qualitative research design with an interpretive phenomenological approach. Data collection strategies used in-depth interview techniques with semi-structured interview guidelines. Researchers conducted data analysis using Interpretative Phenomenological Analysis (IPA). There were four themes in this study, namely 1) Seeking healing in Balian (traditional medicine); 2) Seeking medical health services after treatment at Balian (traditional medicine); 3) Seeking healing in medical and traditional health services together; 4) Reluctant to go to Public Health Center. The results of this study indicate that people are seeking healing to Balian because they believe that possessed by spirits and ancestral curses are the causes of mental disorders, and they are reluctant to go to Public Health Center because of the lack of mental health service quality. \